Effectiveness Analysis of Sevoflurane Combined with Propofol or Remimazolam Anesthesia in Pediatric Laparoscopic Inguinal Hernia Repair and Its Impact on Hemodynamics and Postoperative Pain - Renqi Liu; Zhiyi Wang; Yuanyuan Meng; Weiye Chen; Min Zhou (Journal of Investigative Surgery)
Purpose This study evaluated the clinical effectiveness of combined treatment of sevoflurane with propofol or remimazolam in decreasing hemodynamic changes and postoperative pain in pediatric patients undergoing laparoscopic inguinal hernia repair (LIHR).Methods This study prospectively recruited 287 children with hernia admitted to our hospital from September 2020 to October 2023. These children were allocated into the sevoflurane plus remimazolam and sevoflurane plus propofol groups using the random number table method. General clinical data at admission were collected. Clinical outcomes were compared between the two groups. The primary outcomes included anesthesia quality, intraoperative hemodynamic indicators at different time points (MAP, SpO2, HR), and the postoperative FLACC score, while the secondary outcomes included the PAED score of the children and the incidence of postoperative adverse reactions.Results No remarkable difference occurred between these two groups regarding general clinical data. Compared to the sevoflurane plus propofol group, the sevoflurane plus remimazolam group resulted in significantly lower MAP and HR at T1, T2, T3, and T4 (p < .05), shorter postoperative awakening time (mean difference: 2.9 min, p < .01), lower FLACC pain scores at 0.5, 1, and 2 h postoperatively (p < .05), and lower PAED scores at 5, 15, and 30 min postoperatively (p < .05). Adverse effects were lower in the sevoflurane + remimazolam group (5% vs. 12%, p = .076).Conclusion Sevoflurane plus remimazolam in children receiving LIHR has minimal impact on hemodynamics, reduces pain levels within 4 h postoperatively, lowers PAED and agitation scores, and demonstrates high safety.